Peripheral chemoreceptor responsiveness and hypoxic pulmonary vasoconstriction in humans - Albert, Tyler J; Swenson, Erik R (High altitude medicine & biology, 2014)
Studies in animals have shown that interruption of carotid body afferent hypoxic signaling or efferent CNS activity to the lung enhances hypoxic pulmonary vasoconstriction (HPV). Whether a similar influence of the CNS on HPV strength is present in humans has never been studied, owing to the invasive nature of physical neural ablation or nonspecific systemic effects of pharmacological blockade of putative neural pathways. In order to demonstrate a peripheral chemoreceptor-mediated modulation of HPV in man, we hypothesized that individuals with high hypoxic ventilatory responsiveness, indicative of strong peripheral hypoxic chemosensitivity, should have less HPV in response to inspired hypoxia. In 15 healthy men and women, we measured the normobaric poikilocapnic hypoxic ventilatory response (HVR; L min(-1) % SPo2(-1)) during 15 min of hypoxia (FIo2=0.12). On the following day, we then measured pulmonary artery systolic pressure (PASP) using echosonography while subjects randomly breathed 0.21, 0.18, 0.15, and 0.12 FIo2, each for periods of 15 min. We chose this strategy to obtain an equivalent stimulus for HPV in all subjects, using SPo2 as a surrogate for alveolar Po2. HPV was assessed as PASP at a common interpolated arterial oxygen saturation (SPo2) of 85%. We recorded a sufficient six-fold range of HVR (0.05-0.30, mean 0.13 L min(-1) % SPo2(-1)) similar to previously published data on normobaric, poikilocapnic HVR. HPV at SPo2 of 85% was 28.5 mmHg (range 21.7-41.3). There was a significant inverse relationship between poikilocapnic HVR and HPV (p=0.006, R(2)=0.38). Previous studies of individuals with susceptibility to high altitude pulmonary edema (HAPE) have suggested that both low HVR and high HPV are important risk factors. We show that these two responses are inversely correlated and conclude that a greater magnitude of peripheral chemoreceptor response to hypoxia limits hypoxic pulmonary vasoconstriction in healthy subjects.